2020
DOI: 10.5755/j01.eie.26.3.25744
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Expert System for Earthquake Prediction in Western Himalayan Range

Abstract: Fuzzy Expert System (FES) with application to earthquake prediction has been presented to reproduce the performance of a human expert in earthquake prediction using expert systems. This research aims to predict future earthquakes having a magnitude 5.5 or greater. Previous earthquake data from 2000 to 2019 have been collected for this purpose. Since the earthquake data for the specified region have been reported on different magnitude scales, suitable relationships were determined to obtain uniform data. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…These models were capable to numerically formulate non-linearity of flood due to their data-driven nature without requiring the knowledge of basic physical processes. It has been observed that data-driven models usually make faster predictions with minimal input using ML [47]. Multiple ML algorithms including decision tree (DT) [48], Random Forest (RF) [49] and Gradient Boost (GB) [50] have been applied to improve fault-tolerant accuracy in flood prediction handling more intricate information by applying their complex algorithms in a short time span [51].…”
Section: Related Workmentioning
confidence: 99%
“…These models were capable to numerically formulate non-linearity of flood due to their data-driven nature without requiring the knowledge of basic physical processes. It has been observed that data-driven models usually make faster predictions with minimal input using ML [47]. Multiple ML algorithms including decision tree (DT) [48], Random Forest (RF) [49] and Gradient Boost (GB) [50] have been applied to improve fault-tolerant accuracy in flood prediction handling more intricate information by applying their complex algorithms in a short time span [51].…”
Section: Related Workmentioning
confidence: 99%
“…We have a "data mining" approach for Malicious Software identification and played out some test examination on malware location utilizing Logistic Regression Classifier. The objective of this work is to show genuine consequence of malware identification paces of (LR) [19] [20]. The LR filter is authorized to detect ambiguous examples of malware that may be 74 -83 percent.…”
Section: Related Workmentioning
confidence: 99%
“…The main concern in mobile environment is energy or power. So the mechanisms adapt the applications and helps in saving the energy [9]. All the device which follows mobility have to be scheduling properly with time management mechanism for better efficiency.…”
Section: Distributed Systemmentioning
confidence: 99%